2008
DOI: 10.1021/cg7008732
|View full text |Cite
|
Sign up to set email alerts
|

An Alternate Crystal Form of Gabapentin: A Cocrystal with Oxalic Acid

Abstract: A cocrystal of gabapentin and oxalic acid has been prepared employing a strategy based on a hydrogen-bonded synthon described by the graph set notation R4 2(8). High throughput techniques and solvent drop grinding were used along with traditional crystallization methods, including crystallization in aqueous solutions at various pH. A number of new solid forms have been detected. The cocrystal of gabapentin and oxalic acid was fully characterized including single crystal structure analysis, which revealed the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 24 publications
2
38
0
Order By: Relevance
“…The thermogram of 4 ( Figure 12.a) is characterized by an endothermic peak at 150ºC, corresponding to the melting of the compound. The melting peak is found at a lower temperature than any of the reported polymorphic forms of gabapentin 32 and within the range obtained for other multicomponent forms 33,34 . This peak encloses the cyclisation/ lactamization of gabapentin 32 implying water release that is observed on HSM experiments ( Figure 13) and detected in TGA.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…The thermogram of 4 ( Figure 12.a) is characterized by an endothermic peak at 150ºC, corresponding to the melting of the compound. The melting peak is found at a lower temperature than any of the reported polymorphic forms of gabapentin 32 and within the range obtained for other multicomponent forms 33,34 . This peak encloses the cyclisation/ lactamization of gabapentin 32 implying water release that is observed on HSM experiments ( Figure 13) and detected in TGA.…”
supporting
confidence: 84%
“…An extensive pH stability of gabapentin has been disclosed where an ester derivative obtained at low pH was reported 83 . Multicomponent crystal forms (co-crystals and molecular salts) involving GBP with different carboxylic acids were also recently disclosed 1,[32][33][34] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of cocrystals of APIs with different co-formers formed by different methods have been reported and it was shown that the solid-state interactions between the two compounds are mainly based on hydrogen bonds Childs et al, 2004;Lu and Rohani, 2009;Padrela et al, 2009;Paluch et al, 2011;Trask et al, 2005;Wenger and Bernstein, 2008). We have previously shown that the sulfoxide (S=O) functionality, common in a significant number of APIs, is a potent hydrogen bonding acceptor and forms cocrystals in association with a wide variety of amino (NH) functional groups (Eccles et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Form III is metastable while form IV has not been well-characterized. Co-crystals of gabapentin, with numerous carboxylic acid coformers, have been reported (3,4). A number of studies used Fourier transform infrared spectroscopy (FTIR) to investigate the effect of various processing methods on the polymorphism of gabapentin (2,5).…”
Section: Introductionmentioning
confidence: 99%